Intervertebral Disc-Derived Stem/Progenitor Cells as a Promising Cell Source for Intervertebral Disc Regeneration - Binwu Hu; Ruijun He; Kaige Ma; Zhe Wang; Min Cui; Hongzhi Hu; Saroj Rai; Baichuan Wang; Zengwu Shao (Hindawi Limited, 2018)
Intervertebral disc (IVD) degeneration is considered to be the primary reason for low back pain. Despite remarkable improvements in both pharmacological and surgical management of IVD degeneration (IVDD), therapeutic effects are still unsatisfactory. It is because of the fact that these therapies are mainly focused on alleviating the symptoms rather than treating the underlying cause or restoring the structure and biomechanical function of the IVD. Accumulating evidence has revealed that the endogenous stem/progenitor cells exist in the IVD, and these cells might be a promising cell source in the regeneration of degenerated IVD. However, the biological characteristics and potential application of IVD-derived stem/progenitor cells (IVDSCs) have yet to be investigated in detail. In this review, the authors aim to perform a review to systematically discuss (1) the isolation, surface markers, classification, and biological characteristics of IVDSCs; (2) the aging- and degeneration-related changes of IVDSCs and the influences of IVD microenvironment on IVDSCs; and (3) the potential for IVDSCs to promote regeneration of degenerated IVD. The authors believe that this review exclusively address the current understanding of IVDSCs and provide a novel approach for the IVD regeneration.